Sex dependence of brain size and shape in bipolar disorder: an exploratory study. - Mackay, C; Roddick, E; Barrick, T; Lloyd, A; Roberts, N; Crow, T; Young, A; Ferrier, I (2010)
OBJECTIVES: Anomalies of asymmetry and sex differences in brain structure have frequently been described in schizophrenic illnesses but have seldom been explored in bipolar disorder. METHODS: We measured volumes of the left and right frontal, temporal, parietal, and occipital lobes and computed the magnitude of brain torque (i.e., rightward frontal and leftward occipital asymmetry) for 49 patients with bipolar disorder and 47 healthy controls and performed an exploratory analysis of sex differences in patients and controls. RESULTS: Patients had significantly greater cerebrospinal fluid volume than controls, but no difference in total brain volume. There were no main effects of diagnosis in gray matter lobe volume or brain torque, but when analyses were performed separately for male and female subjects, significant sex-by-diagnosis interactions were found in the volume of the left frontal, left temporal, right parietal, and right occipital lobes, such that male patients with bipolar disorder tend toward larger, more symmetric brains than male controls, whereas female patients tend toward smaller, more asymmetric brains than female controls. CONCLUSION: The lateralised nature of these interactions was such that the normal sex difference in volume was significantly accentuated, whilst the normal sex difference in asymmetry tended to be diminished in patients with bipolar disorder. We conclude that bipolar disorder in part reflects an interaction between brain growth and sex along the anterior-posterior axis of the human brain.